Pengaruh Terpaan Konten dan E-wom di Instagram terhadap Loyalitas Konsumen McDonald Indonesia pada Isu Pemboikotan - Sugiarto, Balqista Adillah (Magister of Communication Science, Sahid University Jakarta., 2024)
This research aims to examine the influence of Instagram content exposure and electronic word-of-mouth (e-WOM) on consumer loyalty towards McDonald's Indonesia, specifically amidst boycott issues. The theoretical framework guiding this study is Social Judgment Theory. Employing an explanatory quantitative method, non-probability sampling was conducted using purposive techniques to select participants who met predefined criteria. Questionnaires were administered to 160 active followers of the @mcdonaldsid Instagram account, all of whom were exposed to boycott-related content and specifically engaged with the